MORPHOLOGY: THE THEORY OF PARTS OF SPEECH IN MODERN ENGLISH (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article explores the role of morphology in the theory of parts of speech in Modern English, providing an in-depth analysis of how words are formed, classified, and function within sentences. The piece begins with an introduction to the basic concepts of morphology and parts of speech, outlining the traditional categories such as nouns, verbs, adjectives, adverbs, pronouns, prepositions, conjunctions, and interjections. It emphasizes the importance of inflectional and derivational morphology in shaping word forms and meanings, illustrating how these morphological processes help identify a word’s grammatical function. The article also highlights the challenges that Modern English presents in classifying words into distinct categories due to phenomena like functional shifts and word flexibility, where a single word may belong to multiple parts of speech depending on its usage (e.g., "run" as both a verb and a noun). Furthermore, the piece examines contemporary linguistic theories, including Generative Grammar and Cognitive Grammar, offering insight into how parts of speech are defined by syntactic distribution and conceptual functions. Additionally, the article addresses the relevance of morphology in computational linguistics, where accurate part-of-speech tagging is crucial for tasks such as machine translation and speech recognition. The piece concludes by acknowledging the importance of understanding morphology and parts of speech in language education, noting that while traditional categorizations remain valuable, a more flexible approach is needed to reflect the dynamic nature of Modern English